Optimalisasi Pengolahan Cabai Menjadi Chili Oil Untuk Meningkatkan Pendapatan Kelompok Wanita Tani - Reza, M. Aulia; Dwi N, M. Zaky; Nur’azkia R, Nazwa; Zakariya, Husni; Alianda W, Najwa; Yuri Is, Manaf; Dilla, Diva Fara; Putri, Inanda; Aditya, M. Ircham; Lestari, Wahyu Tri; Juhari, Juhari (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The community service program in Japanan Hamlet aims to optimize the processing of chili into chili oil products in order to increase the income of the Women Farmers Group (KWT). The local community, who are mostly farmers, often face challenges in utilizing the chili harvest optimally. In order to achieve this goal, this community service activity is carried out through several stages, namely problem identification, solution planning, and program implementation. The methods used in this community service are training and mentoring. The training program includes chili processing techniques, packaging that meets food safety standards, and digital marketing strategies to increase the selling value of the product. The implementation is carried out interactively and based on practice, starting with socialization about the benefits of chili oil and continuing with direct practice. The results of this program show that KWT mothers have increased their knowledge and skills regarding the chili processing process, from selecting raw materials to the packaging stage. In addition, this program also improves the skills of KWT mothers regarding the use of social media and marketplaces as a means of marketing. Despite challenges such as a lack of initial understanding of digital marketing, the solution steps that have been implemented have succeeded in having a positive impact on KWT, which not only gained new knowledge and skills, but also increased their income through value-added products. Through synergy between students, the community, and universities, this activity is expected to provide a significant contribution to the economic welfare of the local community